Information culture formation model of foreign students of engineering and pedagogical specialties - Alieksieieva, H. (Problems of Engineer-Pedagogical Education, 2018)
With the development of information and communication technologies at the present times and the increasing role of information, an essential reserve for improving the education quality of foreign students of engineering and pedagogical specialties is the information culture formation. Taking into account that the process of education an higher education institutions is usually carried out in traditional ways, the process of information culture formation also occurs primarily through means and forms that do not fully correspond to the current level of computer and information technologies development. The article proposes a substantiation of the information culture formation model in accordance with the state of development of modern ICT technologies and taking into account the peculiarities of teaching foreign students of engineering and pedagogical specialties. The result is the information culture formation model, which reflects in three aspects: target-oriented, determined by the content of information culture components; operational, determined by the methods and means of information culture formation; and technological aspect, determined by the sequence of actions reflected in the stages of formation. A well-founded model makes it possible to develop an effective methodology for the information culture formation of foreign students of engineering and pedagogical specialties.